Modern Rhodium‐Catalyzed Organic Reactions 2005
DOI: 10.1002/3527604693.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed [5+2], [6+2], and [5+2+1] Cycloadditions: New Reactions for Organic Synthesis

Abstract: IntroductionOrganic synthesis has played a major role in the advancement of modern science and technology by enabling the preparation of natural and designed targets of chemical, biological, medicinal, environmental, and materials importance [1]. This progress and its continuation toward products of even greater value are unique consequences of the design or discovery and development of fundamentally new reactions. New reactions give rise to new synthetic strategies, which in turn allow for more step-economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…The conversion of intermediate D into cycloheptadiene E is an example of a relatively rare reaction of the cyclopropane-ring expansion through a 1,5-C‒C bond migration [ 15 17 ]. This concerted process is followed by yet another 1,5-migration of the hydrogen atom, leading to the final dimer 2a .…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of intermediate D into cycloheptadiene E is an example of a relatively rare reaction of the cyclopropane-ring expansion through a 1,5-C‒C bond migration [ 15 17 ]. This concerted process is followed by yet another 1,5-migration of the hydrogen atom, leading to the final dimer 2a .…”
Section: Resultsmentioning
confidence: 99%
“…VCP has been frequently employed as a five-carbon component in cycloadditions, which involve cyclometalation then β-carbon elimination or oxidative addition then ring expansion (Scheme 20). 37 On the other hand, VCPs that contain strong electron-withdrawing groups can be ionized by TMs (e.g. palladium) to generate a zwitterionic π-allyl intermediate, which can then couple with Michael acceptors (Scheme 21).…”
Section: Three-membered Ringsmentioning
confidence: 99%
“…A widely studied Rh-catalyzed cycloaddition process is the [5 + 2] reaction between tethered vinylcyclopropanes (VCPs) and alkynes, yielding bicyclo[5.3.0]-fused ring systems (eq ). This process has since been expanded to intra- and intermolecular reactions of VCPs with alkynes, alkenes, and allenes . Later work has shown that ruthenium, iron, nickel, and iridium are also effective catalysts for intramolecular [5 + 2] cycloaddition.…”
Section: Introductionmentioning
confidence: 99%